Perang Wacana Islam Liberal Versus Islam Fundamental - Herdi Sahrasad (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2014)
One of the new phenomenon in religious discourse in Indonesia is the discourse war between liberal Islam versus fundamental Islam. The birth of Liberal Islam has attracted response from fundamental Islam in which the latter use oftenly a hard, crude and rouge language to corner the liberal muslim. This article try to trace back the wrestle and contestation between liberal and fundamental muslim in public sphere to snatch away structure of political opportunity. Whether or not this contestation continues, to some extent this depend on the liberal and fundamental muslim themselves in spreading their influence and teaching in the grassroot level and public sphere.